2021
DOI: 10.3390/pr9020366
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Fractionation of Brewer’s Spent Grain for a Biorefinery Producing Sugars, Oligosaccharides, and Bioethanol

Abstract: Brewer’s spent grain (BSG) is the main by-product of the beer brewing process. It has a huge potential as a feedstock for bio-based manufacturing processes to produce high-value bio-products, biofuels, and platform chemicals. For the valorisation of BSG in a biorefinery process, efficient fractionation and bio-conversion processes are required. The aim of our study was to develop a novel fractionation of BSG for the production of arabinose, arabino-xylooligomers, xylose, and bioethanol. A fractionation process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Another possibility is converting BSG into charcoal bricks, which increases its calorific value from ~ 20 to 27 MJ/kg [87,88]. Multiple works also reported microbial fermentation of brewers' spent grain into bioethanol [89][90][91] or biogas [92][93][94][95], which can be applied as biofuels.…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Another possibility is converting BSG into charcoal bricks, which increases its calorific value from ~ 20 to 27 MJ/kg [87,88]. Multiple works also reported microbial fermentation of brewers' spent grain into bioethanol [89][90][91] or biogas [92][93][94][95], which can be applied as biofuels.…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Similarly, Chen et al [ 48 ] obtained a 69.8% hydrolysis yield in corn cob. Other studies achieved a similar hydrolysis yield of glucose (78%) with lower solid load (15%, w / s ) when BSG was pre-treated by chemical treatments [ 49 ]. However, two sequential chemical treatments with sulfuric acid were performed, which are more polluting than the treatment with ionic liquids [ 50 ].…”
Section: Resultsmentioning
confidence: 86%
“…The maximum XOS yield was 68.5% when XOS were produced by hydrolyzing corncob with 5% propionic acid at 170°C for 50 min ( 52 ). It was reported that the product obtained by hydrolyzing brewer's grains with 1.85% sulfuric acid for 19.5 min contains 6.6 g/L arabinoxylooligosaccharide (AXOS) ( 53 ). The acetic acid pre-treatment of poplar could effectively produce XOS, with a yield of 55.8%, and acetylation degradation of lignin occurred after acetic acid pre-treatment ( 54 ).…”
Section: Preparation Of Xosmentioning
confidence: 99%